DNA methylation and hepatic insulin resistance and steatosis - Sookoian, Silvia Cristina (2012)
Purpose of review: In this review, we show novel evidence about the role of the liver in the development of insulin resistance and suggest that abnormal hepatic triglyceride accumulation is not an innocent bystander comorbidity but adversely affects the peripheral insulin sensitivity. Recent findings: The core of this review is built up around the concept that liver DNA methylation of the peroxisome proliferative activated receptor gamma coactivator one alpha gene promoter modulates the status of peripheral insulin resistance and is strongly associated with plasma fasting insulin levels. We discuss about other mechanisms associated with peroxisome proliferative activated receptor gamma coactivator one alpha regulation, such as an acetylation and deacetylation switch and how these events impact on the liver metabolic function. We suggest a mitochondrial-centric approach to understand the connection between nonalcoholic fatty liver disease and insulin resistance. We finally show new data about how the liver epigenome is modulated by nutritional cues and introduce the role of epigenetics in liver metabolic programming. Summary: The implications of these findings for clinical practice are promising, as the inherent plasticity of epigenetic modifications, produced either physiologically or pathologically, suggests that early therapeutic intervention in patients with fatty liver can potentially revert the systemic phenotype associated with insulin resistance. © 2012 Wolters Kluwer Health | Lippincott Williams & Wilkins.